Isolation of Vibrio vulnificus Serovar E from Aquatic Habitats in Taiwan - Amaro, Carmen (American Society for Microbiology, 1999)
The existence of strains of Vibrio vulnificus serovar E that are avirulent for eels is reported in this work. These isolates were recovered from water and oysters and differed from eel virulent strains in (i) fermentation and utilization of mannitol, (ii) ribotyping after HindIII digestion, and (iii) susceptibility to eel serum. Lipopolysaccharide of these strains lacked the highest molecular weight immunoreactive bands, which are probably involved in serum resistance.